Politeness In Literary Works: An Overview - Ruziyeva Nilufar Xafizovna; Xolova Madina Boboqulovna (Genius Journals, 2022)
For quite a long time the examination of literary works was the domain of literary critics. In the last four decades, however, researchers and linguists began to examine literary texts using pragmatic theories and in so doing, there was a shift in the way in which such texts were analyzed. One of the more prevalent pragmatic theories used in the analysis of literary works is that of politeness theory. Among the many theories on politeness, Brown and Levinson's theory (1978, 1987) is used most often in examining literary texts such as plays, short stories, and novels. One possible reason for its choice as both a theoretical framework and accompanying analytical tool could be that Brown and Levinson's theory of politeness incorporates the perspectives of other theoretical approaches to politeness (e.g., Lakoff, 1973; Fraser and Nolen, 1981; Leech, 1983), as well as findings from empirical studies in the area of politeness (e.g., Shimanoff, 1977; Blum-Kulka, 1987). The primary objective of this chapter is to present an overview of the use of politeness theory, in general, and Brown and Levinson’s, in particular, as an analytical tool in examining literary discourse and modifications made to it by more recent works in the field. Moreover, the chapter focuses on the application of politeness theory in analysing fictional characters' verbal interactions and the ways in which politeness in these interactions are read as linguistic or verbal manifestations of their character.
Keywords: Politeness Theory; Literary Texts; Linguistic Politeness; Sociological Variables